Prevalence of Pediatric Onset Multiple Sclerosis in Saudi Arabia. (9th November 2021) - Bunyan, Reem; Al Towaijri, Ghada; Al Otaibi, Hessa; Kareem, Abid; Algahtani, Hussein; Al Mejally, Mousa; Almubarak, Ali; Alrajeh, Saad; Cupler, Edward; Qureshi, Shireen; Alawi, Sadaga.; Kalakatawi, Mamdouh; et al.
Abstract : Background . The prevalence of multiple sclerosis (MS) appears to be increasing worldwide. However, data on the pediatric onset of MS is lacking, particularly in developing countries. Objective . This study is aimed at reporting the current burden of the pediatric onset of MS in the five regions of Saudi Arabia. Methods . This study used relevant data from the National Saudi MS Registry that was operational between 2015 and 2018. The data on patients with pediatric onset MS from all the hospitals included in the registry was retrospectively analyzed using the age of diagnosis. Patients who were 1-18 years old when diagnosed were included in the analysis. Results . The registry included 287 patients with pediatric onset MS, with a mean age of diagnosis at 15.7 (SD: 2.06). 74.2% of the participants were females. For the included hospitals, the estimated prevalence of pediatric MS was at 2.73/100, 000 pediatric Saudi population. The prevalence of pediatric MS in the remaining nonparticipant hospitals was then projected taking into account both the size of pediatric population in the Kingdom per region and the number of facilities treating and managing MS in each of the corresponding regions. The overall projected prevalence was found to be 14.33/100, 000 Saudi pediatric population. Conclusion . To the best of our knowledge, this study reported the latest epidemiological data of pediatric onset of MS in Saudi Arabia. The current prevalence of MS among the pediatric Saudi population was found to be 2.73/100, 000, and the overall projected prevalence was estimated at 14.33/100, 000. Our findings were similar to those in other pediatric MS cohorts. Further studies are needed to understand the long-term prognosis, response to treatment, and disease course.